Our Sunshine place: A collective narrative and reflection on the experiences of a mental health crisis leading to an admission to a psychiatric inpatient unit. (19th June 2018) - Wyder, Marianne; Roennfeldt, Helena; Rosello, Rise Faith; Stewart, Bridie; Maher, John; Taylor, Rosslyn; Pfeffer, Amanda; Bell, Peter; Barringham, Neil; ,
Abstract: Acute mental health inpatient units are complex environments where tensions between clinical and personal recovery can be amplified. The focus for mental health staff is often centred on providing clinical care, whereas from the patient perspective, the admission can represent a profound existential crisis. There are very few user‐led accounts of their experiences of psychiatric inpatient unit. This project was developed in the traditions of Analytic Auto‐Ethnography, a research methodology which provides a systematic process to reflect on our own experience while still producing trustworthy findings. Through this process, a collective narrative and critical reflection of a group of over 20 individuals with experiences of either providing or receiving care in an acute psychiatric inpatient unit was developed. The narrative developed shows that for some the hospital admission was a time of healing; for others, the inpatient unit represented an alien and unsafe environment, which accentuated the strangeness of the experiences of mental ill health. Common themes among the group were that of an overarching need to make sense of what happened leading up to the admissions and to come to terms with the potential impact of the illness on identity and future. This journey can be best described as a process of healing and moving towards 'wholeness'. Safety, connection, autonomy and control were identified as factors which either facilitated or hindered the process of successfully integrating the various experiences.